College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Chapter P Review - Exercises - Page 77: 111



Work Step by Step

We solve the equation: $\displaystyle \frac{x+1}{x-1}=\frac{2x-1}{2x+1}$ First we cross-multiply: $(x+1)(2x+1)=(2x-1)(x-1)$ Next we distribute: $2x^{2}+3x+1=2x^{2}-3x+1$ And simplify: $2x^{2}-2x^{2}+3x+3x+1-1=0$ $6x=0$ $x=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.